Dietary supplementation with Chinese herbal mixture extracts enhances growth performance, immunity, antioxidant capacity, and intestinal microbiota function in calves - Zhang, Mingxi; Shen, Di; Wu, Yongxing; Dang, Donghe; Dong, Shuwei; Zhang, Jingyan (Frontiers in Veterinary Science, 2025)
This study examined the effects of dietary supplementation with Chinese herbal mixture extracts (CHE) on growth performance, Immunity, antioxidant capacity, and gut microbiota composition in dairy calves. CHE is a compound extracts powder composed of Honeysuckle, Astragalus, Officinal magnolia bark, and Tangerine peel. Forty calves were randomly assigned to four groups: basal diet (CON), basal diet + 0.1% CHE (LCHE), basal diet + 0.2% CHE (MCHE), and basal diet + 0.4% CHE (HCHE). The experiment was conducted for 56 days with daily observations, bi-weekly weighing, blood sampling, and fecal collection toward the end. The addition of the CHE group significantly increased the average daily weight gain (ADG) and decreased the feed/gain ratio (F/G) compared to the CON group (p < 0.05). The apparent digestibility of crude fat, neutral detergent fiber, and acid detergent fiber was higher in HCHE and MCHE groups (p < 0.05). Serum GH and IGF-1 levels increased in MCHE and HCHE groups (p < 0.05). The blood biochemical analysis revealed that the levels of CA and GLU in the MCHE group were higher than those in the CON group, while remaining within the normal physiological range. Both the IgG and IFN-γ levels and the serum antioxidant levels were significantly increased in the CHE supplementation group compared with the control group (p < 0.05). High-throughput 16S rRNA sequencing revealed changes in gut microbiota, with increased unclassified Muribaculaceae and UCG-005 species in MCHE and HCHE groups (p < 0.05). In conclusion, CHE supplementation enhanced digestion, growth performance, immunity, and gut microbiota balance in calves without toxic side effects.Considering both the economic benefits and the effects of the additive, a clinical dosage of 0.2% CHE additive may be recommended.